Implementasi Pembelajaran Power Poin dalam Meningkatkan Pembacaan Kitab Kuning di Pondok Pesantren Fathul Ulum Jombang - Hermanto Hermanto; Imam Syafi’i (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research uses a qualitative research approach design with a qualitative descriptive research type. Data was collected through observation, interviews and document analysis. The sources for this research were the principal, homeroom teacher, students, and Nahwu and Shorof teachers of the Ulya class at the Fathul Ulum Islamic boarding school in Jombang.The research method used is qualitative research. Data collection uses observation, interview and documentation techniques. Data analysis techniques, researchers use data reduction, data presentation, and drawing conclusions or verification. To test the validity of the data, researchers used source triangulation.The results of the research show that, the implementation of power point learning in increasing the reading of the yellow book at the Fathul Ulum Jomba Islamic Boarding School: 1) The implementation of power point learning in increasing the reading of the yellow book at the Fathul Ulum Islamic Boarding School is creating learning tools, adjusting the theme or learning material, implementing the learning power points, and evaluating power point learning; 2) The implication of power point learning in increasing the reading of the yellow book at the Fathul Ulum Diwek Jombang Islamic boarding school is that there is a change in students' understanding and student involvement in the sense that students are actively involved and more enthusiastic in learning.